Regulation Fair Disclosure and Earnings Information: Market, Analyst, and Corporate Responses - Bailey, Warren; Li, Haitao; Mao, Connie X.; Zhong, Rui (Journal of Finance, 2003)
Abstract With the adoption of Regulation Fair Disclosure (Reg FD), market behavior around earnings releases displays no significant change in return volatility (after controlling for decimalization of stock trading) but significant increases in trading volume due to difference in opinion. Analyst forecast dispersion increases, and increases in other measures of disagreement and difference of opinion suggest greater difficulty in forming forecasts beyond the current quarter. Corporations increase the quantity of voluntary disclosures, but only for current quarter earnings. Thus, Reg FD seems to increase the quantity of information available to the public while imposing greater demands on investment professionals.